2007
DOI: 10.1523/jneurosci.4456-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Olig1 and Sox10 Interact Synergistically to DriveMyelin Basic ProteinTranscription in Oligodendrocytes

Abstract: The oligodendrocyte lineage genes (Olig1/2), encoding basic helix-loop-helix transcription factors, were first identified in screens for master regulators of oligodendrocyte development. OLIG1 is important for differentiation of oligodendrocyte precursors into myelinforming oligodendrocytes during development and is thought to play a crucial role in remyelination during multiple sclerosis. However, it is still unclear how OLIG1 interacts with its transcriptional cofactors and DNA targets. OLIG1 was reportedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 38 publications
(79 reference statements)
6
136
0
6
Order By: Relevance
“…Sox9 and Sox10 are two highly related group E Sox proteins, and both are implicated in OL development, but at different stages. Sox9 is known to exert a strong influence on the initial specification of OLs (Stolt et al, 2003), whereas Sox10 plays a key role in promoting terminal OL differentiation (Li et al, 2007a;Stolt et al, 2002). We found that overexpression of Olig1 and Olig2 resulted in a significant increase in Sox9 expression (P < 0.05 vs. GFP group and P < 0.01 vs. Olig1 group) (Fig.…”
Section: Changes In the Expression Of Ol-lineage Related Transcriptiomentioning
confidence: 58%
See 2 more Smart Citations
“…Sox9 and Sox10 are two highly related group E Sox proteins, and both are implicated in OL development, but at different stages. Sox9 is known to exert a strong influence on the initial specification of OLs (Stolt et al, 2003), whereas Sox10 plays a key role in promoting terminal OL differentiation (Li et al, 2007a;Stolt et al, 2002). We found that overexpression of Olig1 and Olig2 resulted in a significant increase in Sox9 expression (P < 0.05 vs. GFP group and P < 0.01 vs. Olig1 group) (Fig.…”
Section: Changes In the Expression Of Ol-lineage Related Transcriptiomentioning
confidence: 58%
“…6C). It has been reported that Sox10 plays a key role in promoting terminal OL differentiation and it also regulates MBP gene expression directly or in combination with Olig1 (Li et al, 2007a;Stolt et al, 2002). The proportion of Sox10 positive cells was also markedly increased by Olig1 and Olig2 overexpression in the injured spinal cord, suggesting that the robust effects of Olig1 and Olig2 on OL maturation may be mediated by Sox10.…”
Section: Olig1 and Olig2 Cooperatively Regulate The Differentiation Omentioning
confidence: 97%
See 1 more Smart Citation
“…In zebrafish, the specification of peripheral neurons relies on Sox10 function (Carney et al, 2006). Additionally, the formation of glial populations, both peripherally and centrally, is regulated by Sox10 across species (Dutton et al, 2001b;Li et al, 2007;Liu et al, 2007;Svaren and Meijer, 2008). Although our Disc1 morphants have fairly normal peripheral neuronal populations, there is a dramatic increase in the number of peripheral glia.…”
Section: Disc1-dependent Transcriptional Repression Of Foxd3 and Sox1mentioning
confidence: 92%
“…Here, we use zebrafish, which have recently become established as a powerful model for the study of glial cells and myelinated axons (Brosamle and Halpern, 2002;Buckley et al, 2010;Kazakova et al, 2006;Kirby et al, 2006;Li et al, 2007;Lyons et al, 2009;Monk et al, 2009;Pogoda et al, 2006;Takada and Appel, 2010), to study the role that axons play in regulating CNS myelination in vivo. As is the case in mammals, we show that single oligodendrocytes in zebrafish myelinate either a small number of large caliber axons or a larger number of smaller axons.…”
Section: Introductionmentioning
confidence: 99%